Study on the Molecular Reactivity of the Dansylglycine in Water and Dioxane Estimated through Conceptual DFT - Norma Flores-Holguin; Juan Frau; Daniel Glossman-Mitnik (New Innovations in Chemistry and Biochemistry Vol. 1, 2021)
This study evaluated a fixed long-range corrected range-separated hybrid (RSH) density functional associated with the Def2TZVP basis set alongside the SMD solvation model for the computation of the structure, molecular properties and chemical reactivity of the M8 intermediate melanoidin pigment in the presence of water an dioxane. The preference of the active sites pertinent to radical, nucleophilic and electrophilic attacks is made through linking them with the electrophilic and nucleophilic Parr functions, Fukui function indices, and condensed Dual Descriptor which are chemical reactivity descriptors that arise from Conceptual Density Functional Theory. The study confirmed the results from previous works showing that the MN12SX density functional is the most appropriate in predicting the chemical reactivity of this molecule in both solvents.